INTRALINGUAL TRANSLATION: A SIMPLIFIED VERSION OF THE ORIGINAL NOVEL DAVID COPPERFIELD - Fani Hafizah; Syahron Lubis; Muhizar Muchtar (Universitas Islam Sumatera Utara (UISU), 2020)
The objectives of this project are to describe the intralingual translation techniques used in translating the original novel David Copperfield into a simplified version and to find out the reasons why the translator made a simplified version of the original novel David Copperfield written by Charles Dickens. This study used the descriptive qualitative method. The data were collected by reading the novel, comparing the original and simplified texts of David Copperfield, identifying, classifying, counting, and concluding the results. The theory of Jakobson was used to analyze the data related to intralingual translation techniques. The results of the study showed that from the total data (20 texts from the original novel David Copperfield and 20 texts from the simplified version), the paraphrasing technique was used 6 times and the summarizing technique was used 14 times. Besides, the most dominant intralingual translation technique used by the translator is the summarizing technique. The reasons why the translator used paraphrasing and summarizing techniques in making the intralingual translation of the original novel into a simplified version were also found. Firstly, the original novel consists of 750 pages, which are easier to read by making the summary of the novel into 238 pages using the summarizing technique. Secondly, the original novel consists of many difficult words, which can hinder the comprehension of the reader whereas in the simplified version the novel was paraphrased by using the paraphrasing technique.